1998
DOI: 10.1074/jbc.273.28.17651
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Protein Interacts with Heterogeneous Nuclear Ribonucleoprotein K

Abstract: Hepatitis C virus (HCV) core protein, a component of viral nucleocapsid, has been shown to modulate cellular and viral promoter activities. To identify potential cellular targets for HCV core protein, a human liver cDNA library was screened for core-interacting proteins using the yeast two-hybrid system. Among the proteins identified was heterogeneous nuclear ribonucleoprotein K (hnRNP K), which has been demonstrated to be a transcriptional regulator. The interaction of HCV core protein with hnRNP K was confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(122 citation statements)
references
References 61 publications
3
117
0
2
Order By: Relevance
“…It can modulate cellular and viral promoter activities, [31][32][33][34] bind to host RNA helicase to interfere with host RNA translation, and interact with host. 35 Recent data has suggested that HCV core may mediate an immunosupressive effect in vivo. In addition, core can directly bind TNF-␤ receptor and may modify the host response to HCV facilitating persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…It can modulate cellular and viral promoter activities, [31][32][33][34] bind to host RNA helicase to interfere with host RNA translation, and interact with host. 35 Recent data has suggested that HCV core may mediate an immunosupressive effect in vivo. In addition, core can directly bind TNF-␤ receptor and may modify the host response to HCV facilitating persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Expression vectors for pSG5.HA.PRMT1, pSG5.HA.CARM1, pSG5.HA.Zac1, pSG5.HA.GRIP1, pSG5.HA.p53, pSG5.HA.hnRNP K, pcDNA3.Flag.hnRNP K, pET3a-HCV Core, pcDNA.HCV Core 1-115 , pSV.AR 0 for the human AR, pHE0 for the human ERa, and Gal4DBD.hnRNP K 338-363 were created as described previously [10][11][12][13]. Arginine to lysine mutant (hnRNP K 5RK) was generated by site directed mutagenesis using wild-type pSG5HA.hnRNP K as the template (Stratagene, USA).…”
Section: Plasmidsmentioning
confidence: 99%
“…Expression vector for yeast protein-arginine methyltransferase, RMT1, was a gift from Dr. Stallcup MR (University of Southern California, LA, USA) [14]. Reporter genes MMTV-LUC, EREII-LUC, GK1, and p21-LUC and bacterial expression vectors for GST-Zac1, GST-PRMT1, GST-CARM1, and GST-hnRNP K were described previously [10][11][12][13]15]. …”
Section: Plasmidsmentioning
confidence: 99%
“…Apart from acting as the basic building block of viral nucleocapsid, it also interacts with a variety of cellular factors, interfering with their normal functions (Lai and Ware, 2000;Ray and Ray, 2001). For instance, HCV core protein has been shown to target several cellular transcription factors such as hnRNP K (Hsieh et al, 1998), LZIP (Jin et al, 2000), 14-3-3 (Aoki et al, 2000), p21/WAF1 , and RNA helicase CAPRf (You et al, 1999), resulting in the alterations in the responsive transcription regulatory activities. Moreover, HCV core protein is able to cooperate with ras oncogene in the transformation of rodent fibroblasts under certain conditions (Chang et al, 1998), to influence host cell growth and proliferation through different mechanisms (Aoki et al, 2000;Cho et al, 2001;Erhardt et al, 2002), to promote immortalization of primary human hepatocytes (Ray et al, 2000), and to cause HCC formation at the late stage of transgenic mice (Moriya et al, 1998).…”
Section: Introductionmentioning
confidence: 99%